521 Immune regulatory metabolites in human ovarian cancer. (9th November 2020) - Lum, Julian; Kilgour, Marisa; MacPherson, Sarah; Zacharias, Lauren; Keyes, Sarah; Allard, Bertrand; Smazynski, Julian; Watson, Peter; Stagg, John; Nelson, Bradley; Deberardinis, Ralph; Hamilton, Phineas
Abstract : Background: Immune regulatory metabolites are key features of the tumor microenvironment (TME), yet with a few exceptions, their identities remain largely unknown. Importantly, little is known about the heterogeneity of metabolites that are present or absent in specimens from human tumors and immune compartments. Methods: Here, we profiled tumor and T cells from tumor and ascites of patients with high-grade serous carcinoma (HGSC) to uncover the metabolomes of these distinct TME compartments. We devised a stringent and robust protocol to enrich cell populations from surgically resected samples in patients with HGSC. We conducted mass spectrometry-based analysis and developed machine learning tools to highlight novel metabolites that are present in different cellular lineages of the tumor. Results: Cells within the ascites and tumor had pervasive metabolite differences, with a striking enrichment in 1-methylnicotinamide (MNA) in T cells infiltrating the tumor compared to ascites. Despite the elevated levels of MNA in T cells, the expression of nicotinamide N-methyltransferase, the enzyme that catalyzes the transfer of a methyl group from S-adenosylmethionine to nicotinamide, was restricted to fibroblasts and tumor cells. T cells treated with MNA stimulated secretion of the tumor promoting cytokine tumor necrosis factor alpha. Conclusions: Our studies provide the first catalogue of metabolites in patient-derived tumors and T cells. We found that TME-derived MNA contributes to the immune modulation of T cells and represents a potential immunotherapy target to treat human cancer. Ethics Approval: This study was approved by the University of British Columbia and BC Cancer Research Ethics Board (H07-00463). Consent: Written informed consent was obtained from the patient to use the results of this study for educational purposes including publications. A copy of the written consent is on file and available for review by the Editor of this journal.